Catheter Related Infections in Pediatric Patients - Herry Garna (Paediatrica Indonesiana, 1993)
During a 9-month prospective study, from August, 1988 to April, 1989, a total number of 4328 hospitalized pediatric patients at the Department of Child Health, Padjadjaran University, Hasan Sadikin General Hospital Bandung, were observed to identify skin and soft tissue nosocomial infections (not included postoperative), especially catheter related injections. The gastroentestinal tract was the most frequent site of nosocomial infections (44.3%), then subsequently followed by skin infection (22.6%), bacteremia (16.3%) and urinary tract infection (14.1%). The most frequent cause of nosocomial skin infections like phlebitis was IVFD occurring in 82 out of 93 patients (88.2%). The overall phlebitis attact rate was 4.2% . When the duration of infusion is devided into 3 groups of 0-36 hours, 37-72 hours and â‰¥ 73 hours, then it becomes clear that the longer the duration of infusion, the higher the attack rate (x2=8.07, p<0.05). Klebsiella pneumonia seemed to be the pathogen most frequently associated with nosocomial skin infections (26. 7%), followed by Enterobacter aerogenes (20.0%), and then E. coli, Ps. aeruginosa and S. aureus 13.3% each. It could be concluded that the risk of contracting phlebitis from JVFD with a duration of â‰¥ 73 hours was. 1.9 times higher than that of less than 72 hours.